The PRC’s UNSC Policy Evolution - A. M. Galimullin (Сравнительная политика, 2021)
The article analyzes the evolution of the PRC's policy in the UNSC under Hu Jintao (2003 – 2013) and Xi Jinping (2013 – present) based on the country’s veto exercising pattern. A study of resolutions and meeting transcripts on the cases of the DPRK, Iran, Myanmar, Zimbabwe, and Syria proves that China’s UNSC veto policy has drastically changed by the end of Hu Jintao's tenure as President – it has become bolder in comparison with that in the early 2000s. An analysis of the veto use after 2013 testiﬁes to the fact that Xi Jinping not only continued the line of his predecessor in the UNSC, but also further developed into an even more proactive one. The cause of such a change lies within two key factors: a signiﬁcant increase in the PRC's capabilities in the international arena, and the adverse effect of the adoption of Resolution 1973 (2011) on Libya. Operating in the UNSC, China is currently guided by the “soft balancing” strategy designed to compete with the United States in the zones of its interests without using military methods, but rather by creating coalitions within international institutions. In the near future, it is possible that this “soft” approach might evolve into a more rigid one.